2020
DOI: 10.1111/desc.12931
|View full text |Cite
|
Sign up to set email alerts
|

Gender gaps in cognitive and social‐emotional skills in early primary grades: Evidence from rural Indonesia

Abstract: Research has shown that gender differences in educational achievement emerge in the early years of school (Cobb-Clark & Moschion, 2017) and can persist into adulthood (Anderson, 2008). There is also a growing body of evidence suggesting that social-emotional skills observed in early childhood affect academic performance and labor market outcomes in later years (Cunha & Heckman, 2008; Cunha, Heckman, & Schennach, 2010). As a result, there is considerable interest in understanding the extent to which gender gaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…This shows many aspects of the relationship between gender and social skills in schools, as shown by the fact that boys and girls do differently in school and in how they act around others. This aligns with the submission of Nakajima et al (2020), who concluded that there were gender differences in cognitive and social-emotional skills, emphasising the importance of understanding and addressing these differences.…”
Section: The Significant Main Effect Of Gender On the Social Skills O...supporting
confidence: 80%
“…This shows many aspects of the relationship between gender and social skills in schools, as shown by the fact that boys and girls do differently in school and in how they act around others. This aligns with the submission of Nakajima et al (2020), who concluded that there were gender differences in cognitive and social-emotional skills, emphasising the importance of understanding and addressing these differences.…”
Section: The Significant Main Effect Of Gender On the Social Skills O...supporting
confidence: 80%
“…This study referred to previous studies and included gender, age, being an only child, preschool education experience, and physical health as control variables in the analysis [ 60 , 61 , 62 , 63 , 64 ]. In terms of gender, a male student had a value of 1 and a female student 0.…”
Section: Methodsmentioning
confidence: 99%
“…Una hipótesis alternativa señala que no hay un efecto mediador sino un efecto moderador de las habilidades socioemocionales en la capacidad cognitiva (Agnoli et al, 2012). También se ha afirmado que las variables socioemocionales impactan de forma diferencial el rendimiento de los individuos condicional al género, la edad y el nivel educativo (Nakajima et al, 2020).…”
Section: Variables No-cognitivas Que Impactan El Aprendizaje De Las M...unclassified